The ethylene receptors CpETR1A and CpETR2B cooperate in the control of sex determination in Cucurbita pepo. (28th September 2019) - García, Alicia; Aguado, Encarnación; Martínez, Cecilia; Loska, Damian; Beltrán, Sergi; Valenzuela, Juan Luis; Garrido, Dolores; Jamilena, Manuel
Abstract: High-throughput screening of an ethyl methanesulfonate-generated mutant collection of Cucurbita pepo using the ethylene triple-response test resulted in the identification of two semi-dominant ethylene-insensitive mutants: etr1a and etr2b . Both mutations altered sex determination mechanisms, promoting conversion of female into bisexual or hermaphrodite flowers, and monoecy into andromonoecy, thereby delaying the transition to female flowering and reducing the number of pistillate flowers per plant. The mutations also altered the growth rate and maturity of petals and carpels in pistillate flowers, lengthening the time required for flowers to reach anthesis, as well as stimulating the growth rate of ovaries and the parthenocarpic development of fruits. Whole-genome sequencing allowed identification of the causal mutation of the phenotypes as two missense mutations in the coding region of CpETR1A and CpETR2B, each one corresponding to one of the duplicates of ethylene receptor genes highly homologous to Arabidopsis ETR1 and ETR2 . The phenotypes of homozygous and heterozygous single- and double-mutant plants indicated that the two ethylene receptors cooperate in the control of the ethylene response. The level of ethylene insensitivity, which was determined by the strength of each mutant allele and the dose of wild-type and mutant etr1a and etr2b alleles, correlated with the degree of phenotypic changes in the mutants. Abstract : Ethylene receptor mutants reveal the involvement of ethylene perception in the control of sex expression, sex determination, and fruit set in Cucurbita pepo .